Gambaran Penggunaan Obat Antihipertensi di Apotek Rawat Jalan Rumah Sakit “X” Tarakan Tahun 2022 - Benyamin; Syuhada Syuhada; Benazir Evita Rukaya (Journal Borneo, 2023)
Hypertension is a global health problem often encountered, and the appropriate use of antihypertensive drugs is very important for optimal blood pressure control. Therefore, it is necessary to research the description of the use of antihypertensive drugs in various health facilities. The purpose of this study was to describe the prescription of antihypertensive drugs in patients at "X" hospital in the outpatient department. The research data obtained were digital data from prescription services from January-December 2022. This study used retrospective data by accessing computer service data at the "X" hospital outpatient pharmacy to track the history of past hypertensive patients’ treatment. The sampling technique used is total sampling. The results showed that the most prescribed antihypertensive drugs were amlodipine, with 13,203 prescription items. Bisoprolol with 10,704 prescription items, and candesartan with 9,885 prescription items. The frequency of prescribing the antihypertensive drug class the most was calcium channel blockers, as much as 13,784 (23.41%), while for the drug class which was the least prescribed, namely alpha-2 agonists, there were 68 drugs (0.12%). Based on the study results, it can be concluded that the most widely prescribed antihypertensive drugs at the outpatient pharmacy at "X" hospital are amlodipine, bisoprolol, and candesartan.